Tensor Two-loop Self-energy Integrals - Khiem, Phan Hong; Son, Do Hoang (Communications in Physics, 2012)
Based on the technique for evaluating tensor two-loop self-energy  integrals in parallel and orthogonal spaces \cite{kreimer94}, we present a new UV subtraction procedure for  a subset of integrals which contains overall UV-divergence. The numerical and analytical results of the sun-rise integral are discussed in comparison with other methods